Một mở rộng bài toán "chiếc túi" - Sinh, Trần Xuân (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall consider the following interger noncovex optimization problem: Minimize cTz, s.t. x Є X. y Є Y, z Є D. zj = xjyj and integer for all j = 1....n where D is a polyhedral convex set in Rn. X = x Є Rn: 0 < a ≤ X ≤ A and Y = y Є Rn: 0 ≤ b ≤ y ≤ B. dTy ≤ e. This problem is reduced to an integer linear programming problem with a convex constraint. The obtained integer problem is solved by a suiable relaxation of its constraints.